Kebijakan Publik dan Politik Hukum dalam Administrasi Pemerintahan - Akmal Priambodo; Husein Satria; Agestanio Yoniv Andana; Siti Arikah Nur Azizah; Muhammad Abrar Dwicofanny; Bagas Setyo Anggoro (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
This article examines the relationship between public policy and legal politics in the context of government administration, focusing on their role in shaping governance quality and administrative effectiveness. Public policy is understood as a political and legal instrument that reflects state choices in regulating power, public interests, and institutional authority. Legal politics provides normative direction that determines how policies are formulated, implemented, and enforced within administrative practices. The study highlights that government administration functions not merely as a technical executor of policy but as a strategic arena where law, politics, and bureaucratic capacity interact. Through an analytical discussion, the article demonstrates that inconsistencies between legal frameworks and administrative implementation often lead to inefficiencies, reduced public trust, and weakened policy outcomes. Contemporary challenges such as decentralization, digital governance, environmental sustainability, and social justice demand innovative policy approaches supported by coherent legal orientation. The findings emphasize that effective government administration requires adaptive legal politics, strong institutional coordination, and a commitment to democratic values. Ultimately, the sustainability of public governance depends on the state’s ability to integrate public policy objectives with a responsive and accountable administrative system.